(untitled) (Bangladesh Journal of Medical Education, 2022)
Since 2009, the portfolio has been a prerequisite for the evaluation of postgraduate residency programs at BSMMU. This descriptive cross-sectional study was conducted with the aim of investigating the current status of portfolio-based training and assessment in BSMMU`s postgraduate training program. Total 264 residents and 30 faculty members selected conveniently and completed the Likert scale-based questionnaire. A checklist was used for reviewing portfolios (n=33) those were preserved by residents. Study revealed that most of the respondents were male (68.6% of residents and 93.3% of faculty members). About 60% of residents have given positive views on presence of instruction and purpose about maintaining the portfolio. Several participants expressed concerns because the portfolio content is self-reported; it may include bias or inaccuracy. Regarding opinions of respondents on characteristics of portfolio, both of the respondents perceived high satisfaction on portfolio based learning, reasonable contents, and practicable and feasible use of portfolio (p<0.05) except regular updating (p<0.05) and comprehensiveness of portfolio. In line with ownership and motivation, faculty members (4.03) highly assumed that the portfolio completed by residents as requirement of the university than residents (3.22) and p<0.05). Residents did not agree that they worked on the portfolio during university deadline (2.89) whereas faculty members ((3.73) showed vary positive views in this regard. Concerning commitments to use the portfolio, both respondents have conveyed high expression (mean >3.5) on the relationship between residents and supervisors so the role of an available supervisor in direct observations of the residents and dedicated educational meetings, giving feedback and support, cannot be exaggerated. Relating to assessment of portfolio, overall views of the respondents have expressed poor to moderate views and faculty members (2.37 to 4.23) have less satisfaction than residents (2.88 to 3.73). Though there are so many constraints such as the lack of clear purposes and instructions, poor understanding regarding ownership, assessment issues, and confusion about educational impact in future, but the portfolio as a feasible and acceptable tool to train and assess clinical competence and clinical specialization. Study recommended for generic format of portfolio based training and assessment to be considered in Bangladesh context. All Stakeholders should be well oriented at the beginning for utilizing the portfolio (supervision, monitoring and assessment system). Bangladesh Journal of Medical Education Vol.13(1) January 2022: 69-78